A `new` old course? An assessment of the effects of alterations to the old course at St. Andrews on the 2015 open championship - Gaudet, C. E. (Journal of Sports Analytics, 2017)
The Old Course at St. Andrews Links is one of the world`s most revered golf courses and the Open Championship is the oldest major championship in professional golf. In 2015 the Old Course hosted the Open Championship. Beforehand, several of the course`s holes were altered in an attempt to maintain its difficulty and counteract the rapid advances in professional golfers` skills and equipment. This study assessed the effects of the alterations to the Old Course in two ways. The aggregate performance statistics for the 2005, 2010, and 2015 Open Championship tournaments, all hosted at the Old Course, were compared. Scoring on the altered holes was compared across the 2010 and 2015 tournaments, as were the differences between the altered and unaltered holes. The analyses took into account the weather conditions. Players` overall scores improved between the 2010 and 2015 tournaments, but not between the 2005 and 2010 tournaments. Players` scores only differed between the 2010 and 2015 tournaments for two of the altered holes, indicating that the changes had a negligible overall effect. Strategic factors that might account for the observed differences and the implications of the analysis for efforts to alter courses to maintain difficulty are discussed.